2011
DOI: 10.1586/eog.11.46
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and the combined oral contraceptive pill: efficacy and effects

Abstract: Obesity and the combined oral contraceptive pill: efficacy and effects "Identifying acceptable, effective birth control for obese women is particularly salient to help prevent unintended pregnancy and obesity-related pregnancy complications … combined oral contraceptives remain among the most effective contraceptive options when taken as directed."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…A study conducted among premenopausal women in Korea and Spain revealed that oral contraceptives (OCs) have a significant association with overweight/obesity 16 17. In contrast other researchers concluded that OC had no association with obesity or weight gain 1 18. Besides; an evidence drawn from a systematic review concluded that there is nosufficient scientific evidence to generalize whether combined oralcontraceptive have significant association with overweight/obesity or not 19…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted among premenopausal women in Korea and Spain revealed that oral contraceptives (OCs) have a significant association with overweight/obesity 16 17. In contrast other researchers concluded that OC had no association with obesity or weight gain 1 18. Besides; an evidence drawn from a systematic review concluded that there is nosufficient scientific evidence to generalize whether combined oralcontraceptive have significant association with overweight/obesity or not 19…”
Section: Introductionmentioning
confidence: 99%